EVALUATION OF TEACHER EMPOWERMENT PROGRAMS IN OPTIMIZING THE QUALITY OF EDUCATION SERVICES USING THE CIPP MODEL - Fairuz, Fathmah; H. Suwiryo, Darmo; Sunarya, Erry (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study aims to evaluate the teacher empowerment program at SMK Ummul Quro Cireunghas, Sukabumi Regency in improving the quality of educational services by considering aspects of context, input, process, and product (CIPP). This study used a qualitative research approach. The sample data source of this study was selected using the snowball sampling technique. Data was collected based on interviews, observations, and documentation. The research findings revealed that (1) the context aspect is good where the teacher empowerment program at SMK Ummul Quro is very helpful for teachers in carrying out their duties and responsibilities as educators; (2) The input aspect is good, the resources allocated in the teacher empowerment program consist of budget costs, facilities and infrastructure, resource persons, cooperation and support from institutions. However, resources in the form of funds and facilities are still limited; (3) the process aspect is good, the empowerment program implementation process is carried out through planning, analyzing teacher professional development needs, program design, resource procurement, selection of facilitators or instructors or resource persons, program implementation, evaluation of results on program effectiveness including feedback from teacher performance, further development or additional training and adjustment of implementation strategies, encouraging teachers to continue learning and developing; (4) The product aspect is good, there have been significant changes as a result of the teacher empowerment program, namely improving teacher performance and improving student learning outcomes, increasing collaboration between teachers, increasing parental involvement, and improving student learning, developing digital learning resources, higher levels of employment. This study recommends that several inhibiting factors need to be improved so that the implementation of educational activities can run smoothly according to the objectives that have been set.